Increased interference fringe visibility from the post-fabrication heat treatment of a perfect crystal silicon neutron interferometer - Heacock, Benjamin; Arif, Muhammad; Cory, David G.; Gnaeupel-Herold, Thomas; Haun, Robert; Huber, Michael G.; Jamer, Michelle E.; Nsofini, Joachim; Pushin, Dimitry A.; Sarenac, Dusan; Taminiau, Ivan; Young, Albert R. (AIP Publishing, 2018)
We find that annealing a previously chemically etched interferometer at 800 degrees C dramatically increased the interference fringe visibility from 23% to 90%. The Bragg plane misalignments were also measured before and after annealing using neutron rocking curves, showing that Bragg plane alignment was improved across the interferometer after annealing. This suggests that current interferometers with low fringe visibility may be salvageable and that annealing may become an important step in the fabrication process of future neutron interferometers, leading to less need for chemical etching and larger more exotic neutron interferometers.
This article may be downloaded for personal use only. Any other use requires prior permission of the author and AIP Publishing. The following article appeared in Heacock, B., Arif, M., Cory, D. G., Gnaeupel-Herold, T., Haun, R., Huber, M. G., … Young, A. R. (2018). Increased interference fringe visibility from the post-fabrication heat treatment of a perfect crystal silicon neutron interferometer. Review of Scientific Instruments, 89(2), 023502. doi:10.1063/1.5008273 and may be found at https://doi.org/10.1063/1.5008273
Keywords: rocking curves; phase-shift; diffraction